2021
DOI: 10.1186/s12889-021-11121-z
|View full text |Cite
|
Sign up to set email alerts
|

Understanding differences within ethnic group designation: comparing risk factors and health indicators between Iranian and Arab Americans in Northern California

Abstract: Background The Middle Eastern and North African (MENA) ethnic group is a diverse group composed of two primary subsets in the United States: Iranian and Arab Americans. We aimed to compare health risk factors, chronic health conditions, and mental health conditions of Iranian and Arab American adults in Northern California. Methods We used cross-sectional electronic health record (EHR) data from a 2016 Northern California health plan study cohort t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…With most older adults having other comorbid chronic conditions that need to be addressed during primary care visits (38), there may be limited opportunities for early detection and screening for ADRD while addressing other health concerns (39). Existing literature has identi ed a wide range (5.5%-60%) of prevalence estimates for depressive symptoms among MENA individuals using community-based convenience samples (40)(41)(42), electronic health record data (43,44), and nationally representative samples (10,45). For example, using linked NHIS and MEPS data, Kindratt and colleagues reported that 38.2% of MENA adults ages 65 and older had depressive symptoms (10).…”
Section: Discussionmentioning
confidence: 99%
“…With most older adults having other comorbid chronic conditions that need to be addressed during primary care visits (38), there may be limited opportunities for early detection and screening for ADRD while addressing other health concerns (39). Existing literature has identi ed a wide range (5.5%-60%) of prevalence estimates for depressive symptoms among MENA individuals using community-based convenience samples (40)(41)(42), electronic health record data (43,44), and nationally representative samples (10,45). For example, using linked NHIS and MEPS data, Kindratt and colleagues reported that 38.2% of MENA adults ages 65 and older had depressive symptoms (10).…”
Section: Discussionmentioning
confidence: 99%